Aluminium sulfate synergistic electrokinetic separation of soluble components from phosphorus slag and simultaneous stabilization of fluoride. (15th February 2023) - Chen, Bangjin; Li, Hailin; Qu, Guangfei; Yang, Jieqian; Jin, Caiyue; Wu, Fenghui; Ren, Yuanchuan; Liu, Ye; Liu, Xinxin; Qin, Jin; Kuang, Lingrui
Abstract: In this study, fluoride (F) was stabilized and soluble components, namely phosphate (P), K, Ca, Cr, Mn, and Pb, were extracted from phosphorus slag (PS) by using aluminum sulfate (AS) synergistic electrokinetic. PHREEQC simulation was used to determine the occurrence form of each ion in the PS. The mechanisms by which various electrokinetic treatment methods affected conductivity and pH distribution were carefully investigated. Electrokinetic treatment increased P concentration of the anode chamber from 22.7 mg/L to 63.39 mg/L, whereas K concentration increased from 15.26 mg/L to 93.44 mg/L. After AS-enhanced electrokinetic treatments, the concentrations of the different components were as follows: P, 131.66 mg/L; K, 198.2 mg/L; and Ca, 331.3 mg/L. The removal rate of soluble P in PS slices increased to 80.88% by 1.5 V/cm of treatment, and it increased to 94.04% after AS enhancement treatment. For water-soluble F, the removal rate from the PS slices in the anode region was 86.03%, decreasing F concentration in the electrode chamber to 9.57 × 10 −3 mg/L. Different extraction efficiencies and stability levels of each component in the PS were regulated at various electrode regions by using different processes such as electromigration, electro-osmotic flow, flocculation, and precipitation. Good results can be obtained if fluoride is solidified concurrently with the removal or recovery of P, K, Ca, and other elements using 2%–4% AS enhanced electrokinetic treatment. Furthermore, CaSO4 ·2H2 O whiskers were produced in the electrode regions when AS content was 6%. The findings of this study indicated that the AS synergistic electrokinetic method is suitable for stabilizing F and removing heavy metals from PS, thus providing a promising technology for recycling valuable components such as P, K, Ca, and Sr and for the simultaneous production of CaSO4 ·2H2 O whiskers. This study provides insights for developing novel technologies for the clean treatment and high-value utilization of PS. Graphical abstract: Image 1 Highlights: Effective removal of soluble impurities in phosphorus slag by electrokinetic. K, P, Ca, Mg, and heavy metals were enriched in different electrode chambers. The removal efficiency of F in the solutions reached 99.93% via AS strengthening. AS synergistic electrokinetic process produced CaSO4 ·2H2 O whiskers. Electromigration, electroosmotic, and electrolysis are the main effect mechanisms.